Overview on current approach on recurrent miscarriage and threatened miscarriage - Sharma, Basant; Deep, Jagat; Pandit, Chandrika; Basnyat, Bina; Khanal, Bandana; Raut, BB; Rajak, Brij Mohan; Patel, Deepak; Laikangbam, Rangina; Basyal, Rajendra (Clinical Journal of Obstetrics and Gynecology, 2020)
Miscarriage is a frequent outcome of pregnancy, with major emotional implications to the couple experiencing such an event. Threatened miscarriage is the commonest complication of early pregnancy and affects about 20% of pregnancies. It presents with vaginal bleeding with or without abdominal cramps. On the other hand recurrent miscarriages are post implantation failures in natural conception. Increasing age of women, smoking, obesity or polycystic ovary syndrome (PCOS) and a previous history of miscarriage are risk factors for threatened miscarriage. The pathophysiology has been associated with changes in levels of cytokines or maternal immune dysfunction. Clinical history and examination, maternal serum biochemistry and ultrasound findings are important to determine the treatment options and provide valuable information for the prognosis. Many surgical and non-surgical interventions are used in the management of threatened and recurrent miscarriages. In this review, we present available evidence-based guidance on the incidence, pathophysiology, investigation and clinical management of recurrent miscarriage and threatened miscarriage, focusing mainly on the first trimester of pregnancy and primary healthcare settings. The review is structured to be clinically relevant. We have critically appraised the evidence to produce a concise answer for clinical practice.